Problem Based Learning Assisted by the Padlet Application on Critical Thinking Abilities and Collaboration Skills - Yuni Masyita Dewi; Astija; I Made Budiarsa (Universitas Pendidikan Ganesha, 2024)
Critical thinking and collaboration skills are essential for students to face the challenges of the 21st century. However, currently, there are still many students who need more critical thinking abilities and collaboration skills, resulting in learning objectives not being achieved optimally. Based on this, this research aims to analyze problem-based learning assisted by the Padlet application on Critical Thinking Abilities and Collaboration Skills. This research is quantitative with a quasi-experimental type of research. This research design uses a non-equivalent control group consisting of experimental and control groups. The sample for this research is the experimental class of 35 students and the control class of 35 students. This research uses data collection techniques, including tests and observations. The data analysis techniques used are the normality test, homogeneity test, and ANOVA test. The results of this research show problem-based learning, assisted by the Padlet application, has a significant influence on critical thinking abilities and collaboration skills. It was concluded that problem-based learning assisted by the Padlet application can improve students' critical thinking abilities and collaboration skills.